Prognostic Value of Tumor Tissue Up-regulated microRNAs in Clear Cell Renal Cell Carcinoma (ccRCC) - Pesta, Martin; Travnicek, Ivan; Kulda, Vlastimil; Ostasov, Pavel; Windrichova, Jindra; Houfkova, Katerina; Knizkova, Tereza; Bendova, Barbora; Hes, Ondrej; Hora, Milan; Topolcan, Ondrej; Polivka, Jiri (In vivo (Athens, Greece), 2024)
BACKGROUND/AIM: The management of patients with clear cell renal cell carcinoma (ccRCC) includes prognosis assessment based on TNM classification and biochemical markers. This approach stratifies patients with advanced ccRCC into groups of favorable, intermediate, and poor prognosis. The aim of the study was to improve prognosis estimation using microRNAs involved in the pathogenesis of ccRCC. PATIENTS AND METHODS: The study was based on a histologically-verified set of matched ccRCC FFPE tissue samples (normal renal tissue, primary tumor, metastasis, n=20+20+20). The expression of 2,549 microRNAs was analyzed using the SurePrint G3 Human miRNA microarray kit (Agilent Technologies). Prognostic value of significantly deregulated microRNAs was further evaluated on microRNA expression and clinical data of 475 patients obtained from TCGA Kidney Clear Cell Carcinoma (KIRC) database. RESULTS: There were 13 up-regulated and 6 down-regulated microRNAs in tumor tissues compared to control tissues. Among them, survival analysis revealed those with prognostic significance. Patients with high expression of miR-21, miR-27a, miR-34a, miR-106b, miR-210, and miR-342 showed significantly unfavorable outcome. The opposite was observed for miR-30e, patients with low expression had significantly shorter survival. CONCLUSION: The inclusion of these microRNAs in a prognostic panel holds the potential to enhance stratification scoring systems, on which the treatment of ccRCC patients is based.
Keywords: Gene Expression Regulation, Neoplastic; nádory ledvin; MicroRNAs; Male; Up-Regulation; karcinom z renálních buněk; prognóza; Neoplasm Staging; mikro RNA; Kaplan-Meier Estimate; regulace genové exprese u nádorů; biomarkers; Kidney Neoplasms; Adult; Kaplanův-Meierův odhad; upregulace; Aged; dospělí; Clear cell renal cell carcinoma; mužské pohlaví; senioři; stanovení celkové genové exprese; treatment; Gene Expression Profiling; senioři nad 80 let; prognosis; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; Aged, 80 and over; microRNA; Prognosis; Carcinoma, Renal Cell; Female; lidé středního věku; staging nádorů; nádorové biomarkery; Middle Aged